Ghana : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Staff is of the view that all criteria have been met, and recommends that the Board determine that Ghana qualifies for immediate debt relief under the MDRI.q.